PKM (Pengabdian Kepada Masyarakat) Lansia Sehat : Lansia Aktif, Mandiri Dan Produktif Di Panti Jompo Basilam - Napitupulu, Natar Fitri (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Community Service (PKM) carried out in this manuscript is the healthy elderly must be empowered so that they can remain healthy and independent as long as possible. One of the efforts to empower the elderly in the community is through the formation and development of Elderly Groups, namely the Elderly Posyandu or Elderly Posbindu. Through this group, the elderly can carry out activities that can keep them active, and motivate the elderly to regulate a healthy lifestyle by following the Healthy Living Community Movement (Germas) and empowering the elderly to have a commitment to live, be active and productive in everyday life. This counseling was carried out to all the elderly living in the Basilam nursing home. They are 25 elderly, which was carried out for one day using LCD, Poster, leafleat and evaluation was carried out by observers using a check list through evaluation through the process and the results of the counseling that all elderly understood and active and committed to doing Germas (Healthy Living Community Movement) and being active and productive in everyday life.